Exporting to China - International Trade Centre (United Nations, 2024)
Since the launch of the Belt and Road Initiative in 2013, exports from participating developing countries to China have soared by 79% to 798 billion. However, almost half of the export potential from these countries to China is unrealized. There are abundant opportunities for export growth in manufacturing exports to China. While many are resource-based, plenty are value-added. Efforts to leverage the former should encompass environmental sustainability and working conditions. Targeted trade promotion must be designed to unlock the latter. Beyond infrastructure improvements, this global initiative promotes international economic cooperation that can materialize sustainable, inclusive, value-added trade for developing countries. The analysis presented in this report provides comprehensive insights into the export potential to the Chinese market for developing countries that participate in the BRI. This report also highlights that while these export opportunities can be a potent force for good, they must be navigated with awareness and foresight, and always with a sustainable development lens. It is not merely about trading more; it is about trading right.